2018
DOI: 10.1002/lary.27133
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of concurrent cigarette, alcohol, and e‐cigarette use: Off‐setting or additive behaviors?

Abstract: 2b. Laryngoscope, 1817-1821, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 21 publications
1
5
0
Order By: Relevance
“…This may have implications for the association between marijuana and ecigarette use in the coming years, and the authors predict that this association will become exacerbated with time. Finally, the association between using alcohol and e-cigarettes has also been noted in other studies [20][21][22]. However, it is unclear what underlies this association.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…This may have implications for the association between marijuana and ecigarette use in the coming years, and the authors predict that this association will become exacerbated with time. Finally, the association between using alcohol and e-cigarettes has also been noted in other studies [20][21][22]. However, it is unclear what underlies this association.…”
Section: Discussionsupporting
confidence: 66%
“…Additionally, e-cigarettes have been associated with a decline in overall health, including lung tissue damage, worse cardiovascular health outcomes and increased inflammatory responses [10][11][12]. Although none in Canada, some international studies have also shown positive associations between risky behaviors such as the use of illicit drugs, marijuana, alcohol and e-cigarette use [13][14][15][16][17][18][19][20][21][22]. Consequently, increased concerns have arisen among substance use researchers since recent e-cigarette designs have grown to accommodate illicit substances.…”
Section: Introductionmentioning
confidence: 99%
“…However, these studies were conducted primarily in convenience samples of young adults and used variable definitions of problematic alcohol use. Other studies have found higher rates of alcohol use in e-cigarette users in epidemiological samples, although these studies utilize relatively narrow assessments of alcohol use (Parikh and Bhattacharyya, 2018, Conway et al, 2018). Additional research is needed to replicate and extend these findings using current alcohol use risk classification systems and diagnostic nomenclature in nationally representative samples (Grant et al, 2015).…”
Section: Introductionmentioning
confidence: 96%
“…In this regard, previous experimental studies have robustly shown that consumption of both alcohol and cocaine use increase the rate of cigarette smoking by enhancing the reinforcing effects of nicotine [39,40]. Third, users of cocaine and alcohol tend not only tend to smoke more, but also frequently consume these substances at the same time [41,42]. It is possible that the repeated pairing of smoking and both alcohol and cocaine use may result in cigarettes being a stimulus that elicits alcohol and cocaine use behavior and vice versa.…”
Section: Discussionmentioning
confidence: 96%